Post‐operative Outcomes in Pediatric Patients Following Facial Reconstruction With Fibula Free Flaps. (2nd June 2022) - Slijepcevic, Allison A.; Wax, Mark K.; Hanasono, Matthew; Ducic, Yadranko; Petrisor, Daniel; Thomas, Carissa M.; Shnayder, Yelizaveta; Kakarala, Kiran; Pipkorn, Patrik; Puram, Sidharth V.; Rich, Jason; Rezaee, Rod; et al.
Abstract : Educational Objective: Assess outcomes of pediatric facial reconstruction with fibula free flaps. Objectives: Free flap reconstruction of complex maxillofacial defects in pediatric patients is rare. Post‐operative complications, donor site morbidity, impact on craniofacial growth, and oro‐dental rehabilitation are unknown. Our study assesses the outcomes of pediatric maxillofacial reconstruction with composite fibula free flaps. Study Design: Retrospective chart review. Methods: Multi‐institutional retrospective chart review from 2000 to 2020 on pediatric patients undergoing maxillomandibular reconstruction with fibula free flaps. Results: Eighty‐seven patients underwent 89 surgeries; 5 maxillary and 84 mandibular defects. Median age: 12 years. Defects were acquired following resection of sarcoma/carcinoma 44% or benign tumors 50%. 73% of cases had immediate free flap reconstruction. Closing osteotomies were reported in 74%; 1 in 40%, 2 in 27%, and more than 2 in 6.7%. Hardware was used in 98% and removed in 25%. 9.2% demonstrated long‐term hardware exposure, greater than 3 months following reconstruction. Short‐term complications: wound infection 6.7%, flap salvage/failure 2.2%, fistula 1.1%, and compromised craniofacial growth: 23%. Two patients developed trismus. Long‐term fibula donor site complications: hypertrophic scarring: 3.4%, dysesthesia: 1.1%, and long‐term gait abnormality: 1.1%. Dental rehabilitation was performed in 33%. Post‐operative speech outcomes showed 94% with fully intelligible speech. Conclusion: Pediatric maxillary and mandible defects repaired with fibula free flaps demonstrated complication rates comparable to the adult free flap population. Long‐term follow‐up did not demonstrate adverse outcomes for craniofacial growth. Hardware for flap retention was utilized and remained in place with minimal exposure. Post‐operative gait abnormality is rare. Level of Evidence: 3 Laryngoscope, 133:302–306, 2023